A maximum fairness consensus model with limited cost in group decision making. (January 2023) - Gong, Gaocan; Li, Ke; Zha, Quanbo
Highlights: We propose a maximum fairness consensus approach with limited cost. We incorporate decision makers' social comparisons and fairness preferences in our model. We explore some properties of individual fairness degree We verify the effectiveness of our model by simulation analyses. Abstract: Fairness has attracted extensive concern in manufacturing, service sector, and government agencies. In group decision making (GDM), decision makers (DMs) may destroy the consensus and reject the final solution when they feel unfair. Therefore, the purpose of this paper is to propose a consensus model which incorporated fairness concern. The paper focus on the fairness of compensations that (DMs) get from moderator in consensus reaching process (CRP). Social comparison theory and Gini coefficient are employed to define the fairness degrees of (DMs). We propose a maximum fairness consensus model with limited cost to provide balanced consensus solution. Meanwhile, some properties of (DMs') fairness are explored. Furthermore, we present a numerical analysis to verify the applicability of the proposed model. Finally, some simulation analyses are used to explore the effectiveness of the proposal.